Menyingkap Tabir Realitas Tax Amnesty - Greska Redielano Ramadan; Nyimas Wardatul Afiqoh (InFestasi, 2018)
Tax amnesty is a shape of government’s programme to increase receiptents from taxsector. Whilst, the effectiveness of these programme need to be evaluated. Datashowed that from taxpayer participation and the target of tax amnesty sides, itdoesn’t in line with what expected. This paper addr essed to reveal the reality of taxamnesty. The meaning realities of tax amnesty would parsed with peeling subjectconsciousness. This research would implicate to figure the meaning of tax amnestyin term to reflect taxpayer compliance phenomenon from the taxpayer and taxconsultant perspectives. This study classified as qualitative research withinterpretive paradigm, whilst, the research methodology used trancendentalphenomenology. This research could discover a few meaning of tax amnesty. Fromthe taxpayer and tax consultant, a few point discovered are tax amnesty is aboutcalculating profit and loss, the existing rules ass if violated, tax amnesty is effectivebut there is the failed side exist, and there is unfair existing within tax amnesty.